PENGARUH LOKASI DAN SUASANA WARKOP TERHADAP KEPUTUSAN PEMBELIAN: (Studi Kasus di Warkop Waras Desa Kuningan Kabupaten Blitar) - Hanik Amaria (Pusat Riset dan Inovasi Nasional, 2022)
The coffee shop business has been growing and mushrooming in the last 5 years. For this reason, various efforts are made to maintain the business or business. The main problem studied in this study is how the location and atmosphere of the warkop influence the buying decision at a sane warkop in Kuningan Village, Blitar Regency. Thus, this study aims to find out how the influence of the location and atmosphere of the warkop has on purchasing decisions at a sane warkop in Kuningan village, Blitar district, either partially or simultaneously. To apply these objectives, this study used a quantitative approach through descriptive statistical testing. Instrument testing includes validity testing, reliability testing and continued with the classical assumption test by carrying out normality testing, hecteroscedasticity testing, and hypothesis testing (T-Test) and F-test (Simultaneous) through a significance level of 5% (0.05). This research resulted in that there is a significant influence both individually and simultaneously on the purchase decision. These results can be seen from the significance value of the T test for the location variable of 0.009 <0.05, then the warkop atmosphere variable which obtained a significance result of 0.014 <0.05, then for the F test obtained a significance result of 0.002 <0.05.